Effect of evidence-based guidelines regarding prenatal activity on maternal and neonatal health outcomes - Asmaa Abobakr Ibrahim; Farida Kamel Yousef (Elsevier, 2022)
Aim: This study aimed to evaluate the effect of evidence-based guidelines regarding prenatal physical activity on maternal and neonatal health outcomes. Methods: This quasi-experimental design (study & control group) was conducted on a convenience sample of 64 pregnant women at the obstetrical outpatient clinic in the Suez Canal University Hospital. The data were collected by structured interview sheet for assessing demographic characteristics, questions for maternal and neonatal outcomes during pregnancy, during and after labor, Apgar score, and knowledge assessment regarding applying physical activity guidelines intervention. Results: Caesarean section was statistically significantly higher in the control group with 12 (37.50 %) compared to 4 (12.50 %) in the physical activity group (p = 0.021). The incidence of intact perineum was significantly higher in women who performed physical activity during pregnancy (40.63 %) than those who did not (12.5 %) (p = 0.010). Regarding grades of physical activity, there was 25 (75 %) women in the physical activity group who had good grades of physical activity at four weeks post-intervention compared to only 1 (3.13 %) in the control group (p < 0.0001), also at eight weeks after the intervention, 29 (90.63 %) in the physical activity group had good grades compared with only 1 (3.13 %) in the control group (p < 0.0001). Conclusion: Prenatal physical exercise has various benefits for mothers, including reduced excessive prenatal weight gain, improved birth course, lower incidence of gestational diabetes mellitus, preeclampsia and reduced bodily discomforts associated with pregnancy. Recommendation: Before, during, and after pregnancy, women with normal pregnancies should be encouraged to engage in aerobic and strength conditioning exercises.